Lactobacillus apis sp. nov., from the stomach of honeybees (Apis mellifera), having an in vitro inhibitory effect on the causative agents of American and European foulbrood - Killer, J; Dubná, S; Sedláček, I; Švec, P (International journal of systematic and evolutionary microbiology, 2014)
A taxonomic study was performed on Gram-stain-positive, catalase-negative and regular rod-shaped bacterial strains R4B(T) and R4C, isolated from the stomachs of honeybees. 16S rRNA gene sequence analysis revealed that the phylogenetic position of the novel strains was within the genus Lactobacillus; the highest sequence similarity to R4B(T) was shown by Lactobacillus acidophilus BCRC 10695(T) (93.6 %). Lower sequence similarities were found to other obligately homofermentative lactobacilli. A PCR-DGGE method could detect the sequence of the 16S rRNA gene of strain R4B(T) at different developmental stages of honeybees occurring in two different locations in the Czech Republic. The distinctiveness of the strains from other lactobacilli was also confirmed by analysis of sequences of other phylogenetic markers applicable to the taxonomy of the genus Lactobacillus, ribotyping and rep-PCR analysis. The DNA G+C content of strain R4B(T) was 41.3 mol%. The predominant cellular fatty acids of strain R4B(T) were C18 : 1ω9c, summed C19 : 1ω6c/C19 : 0 cyclo ω10c, C16 : 0, summed C18 : 1ω7c/C18 : 1ω6c and summed C16 : 1ω7c/C16 : 1ω6c. The major polar lipids of strain R4B(T) were glycolipids, lipids and phospholipids. Phenotypic and phylogenetic characteristics also confirmed the independent status of the strains at the species level. Interestingly, strain R4B(T) was able to inhibit growth in vitro of Paenibacillus larvae subsp. larvae (causal agent of American foulbrood in honeybees) and Melissococcus plutonius (causal agent of European foulbrood). The name Lactobacillus apis sp. nov. is proposed for this novel taxon; the type strain is R4B(T) ( = CCM 8403(T) = LMG 26964(T)).
Keywords: Molecular Sequence Data; Sequence Analysis, DNA; RNA, Ribosomal, 16S; ribotypizace; DNA, Bacterial; techniky typizace bakterií; Česká republika; Enterococcaceae; Fatty Acids; zastoupení bazí; United States; Ribotyping; Czech Republic; Paenibacillus; Stomach; Bacterial Typing Techniques; DNA bakterií; žaludek; RNA ribozomální 16S; zvířata; Base Composition; Phospholipids; fylogeneze; Spojené státy americké; sekvenční analýza DNA; včely; mastné kyseliny; molekulární sekvence - údaje; Antibiosis; Bees; fosfolipidy; Phylogeny; Lactobacillus; antibióza; Animals